An E3‐14.7K Peptide that Promotes Microtubules‐Mediated Transport of Plasmid DNA Increases Polyplexes Transfection Efficiency. Issue 22 (10th May 2013) - Pigeon, Lucie; Gonçalves, Cristine; Gosset, David; Pichon, Chantal; Midoux, Patrick
Abstract Chemical vectors as cationic polymers and cationic lipids are promising alternatives to viral vectors for gene therapy. Beside endosome escape and nuclear import, plasmid DNA (pDNA) migration in the cytosol toward the nuclear envelope is also regarded as a limiting step for efficient DNA transfection with non‐viral vectors. Here, the interaction between E3‐14.7K and FIP‐1 to favor migration of pDNA along microtubules is exploited. E3‐14.7K is an early protein of human adenoviruses that interacts via FIP‐1 (Fourteen.7K Interacting Protein 1) protein with the light‐chain components of the human microtubule motor protein dynein (TCTEL1). This peptide is conjugated with pDNA and mediates interaction of pDNA in vitro with isolated microtubules as well as with microtubules in cellulo. Videomicroscopy and tracking treatment of images clearly demonstrate that P79‐98/pDNA conjugate exhibits a linear transport with large amplitude along microtubules upon 2 h transfection with polyplexes whereas control pDNA conjugate exhibits small non‐directional movements in the cytoplasm. Remarkably, P79‐98/peGFP polyplexes enhance by a factor 2.5 (up to 76%) the number of transfected cells. The results demonstrate, for the first time, that the transfection efficiency of polyplexes can be drastically increased when the microtubules migration of pDNA is facilitated by a peptide allowing pDNA docking to TCTEL1. This is a real breakthrough in the non viral gene delivery field that opens hope to build artificial viruses.